Use of Cellulase enzyme obtained from Monilia (Moniliophthora roreri) for treatment of solid waste of Cob, Rice husks and Cocoa shell - Nataly Solís,Carlos Chiriboga,Rodrigo Ávalos,Darwin Rueda,Cristina Albán,Bangeppagari Manjunatha,Bryan Rueda,Mariadoss Selvanayagam (Journal of Applied Pharmaceutical Science, 2016)
Ecuador generates lots of lingo cellulosic organic waste from cocoa, rice and corn agribusiness, and these products are rich in cellulose and can be used in fermentation processes by enzyme producing yeasts. In this study, the phytopathogenic fungus Moniliophthora roreri was isolated, characterized and the kinetics of production of cellulose was studied using rice husks, cocoa shell and cob as a growth inducer substance for a period of 20 days. The carboxymethylcellulose (CMC) was used as specific substrate to evaluate the kinetic parameters of the enzyme at different concentration of 0.5%, 1% and 1.5%; to evaluate the Vmax, Km, specific activity, Kcat we worked with the Michaelis-Menten and Line weaver-Burk linearization and the crude enzyme was purified with ammonium sulfate. The enzyme production was increased on 10th, 15th and 20th day in rice husk, cocoa shell and cob, respectively. There was also an increased enzyme activity and the kinetic parameters obtained from rice husk. The purification is a step to increase the specific activity of the enzyme in each of the extracts is under study.
Keywords: Moniliophthora roreri,Cellulose,Enzyme activity,Enzyme purification,Kinetic parameters.